Pembuatan Aplikasi Delivery Order Toko Roti Vania Bakery - Michael Antonio; Gregorius Satia Budhi; Kristo Radion Purba (Jurnal Infra, 2017)
Amid the many activities that continue to rise, and time-consuming public to buy food directly to the desired bakery. Then some of the food and bakery through examples of existing cases, birth of a solution by providing messaging services, and to send food to the customer. If there is a case, if a person does not know what the menu is available, then surely someone is forced out of the house and go to the food or bakery it to make sure it directly. By using the application, with the internet on the device or gadget on your laptop or computer, the delivery service can be accessed more practical and very easy to use, as well as other benefits can save time and costs. Application delivery order this bakery, a web-based information system designed with HTML5, providing the process of ordering products from the bakery Vania Bakery. Thus the customers who use the system, can be more convenient ordering process and can save energy and costs. In addition to the application is expected to attract more buyers in order to increase the income of the bakery.